Analysis of employee's work stress as an intervening variable on employee performance effect of PT. UTB uses path analysis method - Denis Firda Khoiriyah; Muhamad Imron Zamzani; Mochamad Sulaiman (LPPMPK- Universitas Muhammadiyah Cileungsi, 2024)
The use of human resources is crucial to every business and organizational activity. Companies have a variety of options for enhancing the quality of their human resources, including raising staff productivity. Employee performance is the work that they do, and the outcomes they produce are in line with the objectives of the business or organization. Employee performance is affected by a number of variables, including workload and job motivation. Additionally, job stress has an impact on how well employees perform. Because of an imbalance between workload and aptitude, someone experiences work stress. Based on this, this study seeks to ascertain the impact of workload and work motivation on employee performance as well as the impact of these factors on employee performance as it relates to work stress at PT.UTB. route analysis or route analysis is the research methodology employed. The extent of the independent factors' impact on the dependent variable through the intermediary variables can be seen using path analysis. The information was gathered from 39 respondents across 50 populations. The analysis's findings indicate that while work motivation has a direct, significant positive impact on employee performance, workload has a direct, significant negative impact. Employee performance is impacted by workload through employee work stress at a PT.UTB of 0.51 and by work motivation through employee work stress at a PT.UTB of 0.83